2021
DOI: 10.3390/ijerph18189940
|View full text |Cite
|
Sign up to set email alerts
|

Performances of Limited Area Models for the WORKLIMATE Heat–Health Warning System to Protect Worker’s Health and Productivity in Italy

Abstract: Outdoor workers are particularly exposed to climate conditions, and in particular, the increase of environmental temperature directly affects their health and productivity. For these reasons, in recent years, heat-health warning systems have been developed for workers generally using heat stress indicators obtained by the combination of meteorological parameters to describe the thermal stress induced by the outdoor environment on the human body. There are several studies on the verification of the parameters p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“… 50 One study highlighted the importance of mobile technology to provide heat safety education for farm workers, 51 and 2 studies discussed the development of heat-health warning systems in the occupational context for the protection of workers. 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“… 50 One study highlighted the importance of mobile technology to provide heat safety education for farm workers, 51 and 2 studies discussed the development of heat-health warning systems in the occupational context for the protection of workers. 52 , 53 …”
Section: Resultsmentioning
confidence: 99%
“…The physiological link between heat exposure and workers concerns both health and productivity [11] and depends on individual characteristics [10] as well as outdoor working conditions [46], that can be, however, mitigated by practices like hydration, work-time shifting, work-rest cycles and ventilated clothing [15,[47][48][49]. In this context, the recent Italian Worklimate project has developed a heat stress forecasting system for different outdoor working scenarios [50], developing informative and training material for employers and workers to help raise awareness and prevent heat stress and injuries among workers (https://www.worklimate.it/en/, accessed on 17 November 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The construction industry is vulnerable to climate change risks because of its dependence on temperature and seasonal conditions. Most construction work is conducted outdoors and is labor-intensive, so workers' health and productivity are directly affected by temperature changes (Grifoni et al, 2021). Kim and Hong's (2020) thermal evaluation questionnaire results indicated that humans function most efficiently and comfortably at 25 °C.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, agricultural and construction workers frequently wear personal protective gear and clothes, especially when engaging in outside tasks. This can dramatically reduce body heat loss and increase heat stress (Grifoni et al, 2021). When air temperature approaches or exceeds skin temperature (31 °C-32 °C), it is almost ineffective for the human body to dissipate heat through natural air convection; instead, sweat evaporation takes over as the primary method of heat dissipation (Hargreaves, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%